(untitled) (Research, Society and Development, 2021)
Fungi are a prolific source of biologically active metabolites, including a wide range of clinically important drugs. Therefore, this study aims to evaluate the antimicrobial and cytotoxic activity of secondary metabolites extracted from fungal mycelia isolated from freshwater samples in the state of Amazonas. Mycelial extracts from 12 fungal were used, extracted with MeOH/AcOEt (1:1) according to the criteria established by Souza et al. (2004). For antimicrobial activity, the extracts were tested against the pathogens Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Enterococcus feacalis, Candida albicans and C. tropicalis. To identify the minimum inhibitory dosage (MID) the microdilution method was used. To perform the cytotoxicity assay, the VERO strain (ATCC® CCL-81TM) was used. The assays were determined by the Alamar Blue method according to Ahmed et al. (1994). The tested extracts did not show antibacterial activity. Five extracts (41.7%), obtained from the fungi Aspergillus - 1283, Chrysoporther - 1169, Diaporther – 1203, Fusarium – 1085, and Trichoderma, showed antifungal activity against C. albicans. Diaporther extract (8.3%) - 1203 was active against C. tropicalis. In the cytotoxicity assay, 58.3% of the evaluated extracts showed no significant toxic effect. Five extracts, Cladosporium - 1135, Chrysoporther - 1169, Cytospora - 1098, Fusarium - 1085, and Talaromyces - 1244, showed cytotoxic potential, exhibiting viability lower than 70%. The results obtained suggest that mycelial extracts of fungi isolated from water samples from the Amazon region have potential against yeasts of medical interest. Only two of the active extracts were revealed potentially cytotoxic.